2007
DOI: 10.1111/j.1551-2916.2007.01592.x
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Defect Fluorite and Pyrochlore Phases in Lanthanum and Gadolinium Hafnates

Abstract: Aerodynamic levitation combined with laser heating was used to prepare melts in the HfO2–La2O3 (–Gd2O3) systems. All melts crystallized upon quenching in oxygen. Hf2La2O7 pyrochlore and Gd0.5Hf0.5O1.75 fluorite phases were identified. Gd0.5Hf0.5O1.75 fluorite was transformed into the pyrochlore structure by annealing at 1450°C. Pyrochlore that crystallized from HfO2‐ La2O3 melts contained 31.6–34.2 mol% La2O3. The unit cell parameter increased linearly with La content from 10.736 to 10.789 Å. Drop solution cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
29
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
10
29
0
1
Order By: Relevance
“…Annealing this phase at 1450°C for 50 h resulted in the formation of the ordered pyrochlore phase. 26 Therefore, the calculated ⌬H f,ox (Hf 0.5 La 0.5 O 1.75 , amorphous) from ⌬H f,ox (fluorite) − ⌬H cryst represents only an approximation.…”
Section: B Energetics Of Pyrochlore Fluorite and Amorphous Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Annealing this phase at 1450°C for 50 h resulted in the formation of the ordered pyrochlore phase. 26 Therefore, the calculated ⌬H f,ox (Hf 0.5 La 0.5 O 1.75 , amorphous) from ⌬H f,ox (fluorite) − ⌬H cryst represents only an approximation.…”
Section: B Energetics Of Pyrochlore Fluorite and Amorphous Phasementioning
confidence: 99%
“…7,20,26 The enthalpy of formation of the amorphous phase was calculated by combining the enthalpy of crystallization with the enthalpy of formation of the fluorite phase:…”
Section: B Energetics Of Pyrochlore Fluorite and Amorphous Phasementioning
confidence: 99%
“…Фазовые диаграммы систем «Ln 2 которые при комнатной температуре могут иметь как кристаллическую структуру пирохлора, так и флюорита [14].…”
unclassified
“…5 It has been demonstrated that Y 2 O 3 doping stabilizes HfO 2 in the cubic phase. [5][6][7][8] Doping of HfO 2 by Er, [7][8][9] Gd, 8,10,11 and many other rare earth elements 8 also induces a monoclinic to cubic phase transition. The gadolinium doping of a number of wide band gap semiconductors [12][13][14] suggested that Gd doping of HfO 2 may lead to a dilute magnetic semiconductor.…”
mentioning
confidence: 99%
“…[8][9][10] The presence of a small amount of the Gd 2 Hf 2 O 7 pyrochlore phase cannot, a priori, be excluded, because it differs from fluorite only in the presence of ordering within the cation sublattice. 8,11 To determine the placement of the Fermi level, temperature-dependent angle-resolved photoemission experiments were performed using the 3 m toroidal grating monochromator beam line in an UHV chamber previously described. 18,19 The Fermi level ͑E F ͒ was established from a a͒ Electronic mail: pdowben@unl.edu…”
mentioning
confidence: 99%